Exploring the economic value of a cloud computing solution and its contribution to green IT. (1st January 2014) - Nedbal, Dietmar; Stieninger, Mark
Cloud computing has become a commonly accepted outsourcing business model in the last couple of years. Additionally, organisations are also becoming more aware of the necessity to adopt 'green' technologies. This article highlights synergistic effects between cloud computing solutions and green IT. After a general introduction, a case study in the field of e-invoicing serves as testimonial for a discussion on aspects concerning the economic value and on potentials regarding energy efficiency. Results from this case indicate that both costs and carbon dioxide emissions can be reduced by more than a half by using an integrated cloud computing solution with still potential remaining when integrating business processes and services on the cross-organisational level.